PS01.027: HYBRID PERORAL—LAPAROSCOPIC ESOPHAGECTOMY: A NOVEL MINIMALLY INVASIVE APPROACH FOR CHRONIC ESOPHAGEAL FISTULA. (14th September 2018) - Vetter, Diana; Bauerfeind, Peter; Schmidt, Henner; Lachat, Mario; Gutschow, Christian
Abstract: Background: Chronic esophageal fistula represents a challenging clinical scenario. Surgical therapy is associated with extreme morbidity and high mortality. Our aim was to minimize surgical trauma, introducing a combined peroral and laparoscopic approach for esophagectomy. Methods: Case presentation of a 51-year-old patient with graft infection due to an esophago-periprosthetic fistula 2.5 years after aortic root replacement. Surgical revision of the aortic root with simultaneous esophagectomy was deemed too invasive in this case. Therefore, a minimally invasive peroral and laparoscopic approach for esophagectomy and exclusion of the infected graft was chosen. Technically, a vagus-sparing transhiatal esophageal dissection was performed laparoscopically, followed by an upper mediastinal esophageal dissection via a left cervical approach. A short esophageal segment 5cm above and below the fistula was not dissected, but here a peroral endoscopic mucosectomy was performed. After insertion of a gastric feeding tube, the stomach was transsected laparoscopically and the mobilized distal esophagus was removed. Then, the proximal portion of the esophagus was divided just above the fistula and diverted via a left cervical esophagostomy. Results: After an uneventful postoperative course, the patient was discharged under antibiotic coverage with amoxicillin, clavulanic acid and minocyclin. At follow-up, the patient remained stable without clinical signs of infection. Seven months later, he underwent minimally invasive retrosternal reconstruction with a gastric pullup and cervical end-to-side esophago-gastrostomy. Conclusion: To our best knowledge, this is the first clinical report of a successful hybrid peroral endoscopic and laparoscopic approach for esophagectomy. This procedure may be a viable and less invasive alternative for patients with chronic esophageal fistula. Disclosure: All authors have declared no conflicts of interest.